MCB earth leakage fault detection scheme based on global system for mobile communication using Arduino Uno - Ashari, Ahmad Asraf; Mohamad, Nor Zulaily; Mohammad Radzi, Nur Hanis (Penerbit UTHM, 2020)
Electrical safety and hazard were always taken as a priority during the utilization of home appliances. Some people that are not aware of the electrical safety inspection will initiate fault and produce an electrical shock [1]. Each home will be provided with a home distribution board to distribute the current to all the loads in the house. The electrical energy that flows from the distribution board will get consumed by home appliances when the switch inlet is turned on.